Conditions of minimum wage indexation in Czech and Slovak legislation in the context of business economics - Martin Pernica (DANUBE: Law, Economics and Social Issues Review, 2016)
The aim of the article is to assess - on the basis of a comparison of Czech and Slovak legislation relating to the conditions of the minimum wage indexation - whether it would be appropriate to use certain aspects of Slovak legislation in the Czech legislation and vice versa. When elaborating the article, some logical methods were used. In order to collect data, important employers were addressed in the South-Moravian Region. A carrying method used during the work was a comparison. Analyses were processed using the data of the Czech Statistical Office, the European Statistical Office and the Ministry of Labour and Social Affairs of the Czech Republic. To evaluate the research, the percentage representation of positive and negative responses and Pearson's Chi-square test were used. The paper presents the results of research whose aim was to get the views of entrepreneurs regarding the minimum wage level and conditions of its indexation. Employers supported the idea of maintaining the institution of the minimum wage. A predominant portion of companies would welcome it if the minimum wage were derived on the basis of an average wage, and the vast majority of companies would welcome the annual indexation of the minimum wage by inflation.
Keywords: 330; Kaitz Index; Minimum Wage; Tripartite; Law on a Minimum Wage